The association of foot posture and osteoarthritis of the medial compartment of the knee joint: A literature review - Shrikant Wagh; Rizwan Razak (Indian Journal of Rheumatology)
Osteoarthritis (OA) of the knee joint (KOA) is a major cause of morbidity among older adults. Medial compartment KOA (MCKOA) is the more common form. High body mass index (BMI), obesity, and older age are some of the risk factors for KOA. Adult acquired pronated foot deformity is another common condition with some common risk factors. This systematized review aims to assess the association of MCKOA and posture of the foot and the impact of assessment of foot posture in the management of MCKOA. A search was carried out from PubMed, Cochrane, and Google Scholar for studies related to the association of foot posture and MCKOA. 11 studies (out of 5926) that met the inclusion criteria were selected for analysis. These studies (3685 participants) were divided into two subgroups: (a) studies of association of foot posture with MCKOA (n = 8) and (b) studies of association between foot pain and knee pain/osteoarthritis (n = 3). The studies are heterogeneous due to different methods of foot posture assessment, KOA diagnosis, and noninclusion of covariates such as age, gender, and BMI. These studies indicate that there is an association between pronated foot posture and MCKOA. There is insufficient evidence to determine the impact of foot posture assessment in the management of MCKOA. An assessment of foot posture followed by correction with customized orthoses may help relieve pain in some of these patients. It is, therefore, essential to assess the foot posture in all patients of KOA.